TATA KELOLA KEUANGAN DESA SIDULANG KECAMATAN LAGUBOTI KABUPATEN TOBA TAHUN 2023 - Pangaribuan, Hormat Jaeran; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
In carrying out governance, the village government has the authority to regulate the use of village finances, prioritizing them to fund village development, community empowerment, and community development. Village financial management is defined as the entirety of activities encompassing planning, budgeting, implementation, administration, reporting, accountability, and financial guidance and supervision. However, community participation in planning in Sidulang Village remains low. This study aims to determine the financial governance of Sidulang Village in 2023. This study employed a qualitative approach with descriptive methods. Data collection techniques included interviews and documentation. The informants included the village government, the Head of the Village Government Division of the Toba Regency PMDPPA Service, the inspectorate, and the Sidulang Village community. This study utilized the village financial governance theory of Muhamad Mu'iz Raharjo (2020). Research on Sidulang Village's financial governance in 2023 indicates that financial management in Sidulang Village has not been optimal. This is evident in the low level of community participation in planning. Village officials' ability to operate the SISKEUDES application and prepare reports remains inadequate. Keywords: Village, Village Finance, Governance